Factors Influencing Dropout and Retention Among Autistic Students in Universities: A Meta-Synthesis of Qualitative Studies Involving Autistic Individuals - Oriyomi Shittu; Georgia Smith; Megan Freeth (BJPsych Open, 2025)
Aims: Approximately 2% of students in higher education are diagnosed with autism, a figure likely underreported due to non-disclosure and diagnostic challenges. Autistic students in higher education face unique challenges that impact their academic persistence and success. These students experience higher dropout rates compared with their neurotypical peers. Identifying the factors leading to high dropout rates is essential for developing interventions that promote a more supportive academic environment for autistic students.